EFEKTIVITAS PERATURAN OTORITAS JASA KEUANGAN NOMOR 9/ POJK.04/2015 TAHUN 2015 TENTANG PEDOMAN TRANSAKSI REPURCHASE AGREEMENT BAGI LEMBAGA JASA KEUANGAN (STUDI KASUS TRANSAKSI REPO SAHAM BENNY TJOKROSAPUTRO TAHUN 2016) - Debora Kezia Wijaya; Christine S. T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2019)
Effectiveness is a situation that shows how the achievement of something with both time and good result. Effectiveness of government regulation means that the regulators have succeed implementing and applying the regulation in society. The effectiveness of government regulation is also apparent from whether the objective of the regulation is sufficient or not. The Financial Services Authority has made the Repurchase Agreement Transaction Regulation in 2015, which known as Financial Services Authority Regulation Num. 9/POJK.04/2015 Concerning Guideline of Repurchase Agreement Transaction for Financial Services Institution. Repurchase Agreement Transaction hereinafter referred to as Repo Transaction is a contract of selling or buying Securities with a commitment to sell or buy them back at the appointed time and price. The Repo Transaction is one of transaction in Indonesia’s Capital Market. Repo Transactions are essentially type of transactions that can be considered as selling and buying Securities, but actually Repo Transaction is not same as selling and buying Securities in general. Differences between Repo Transaction and selling and buying Securities also seen in the effect of the Repo Transaction itself, each Repo Transaction shall result in a change of ownership of Securities. There had been a dispute in 2016 related to Repo Transaction between Benny Tjokrosaputro and an Investment Bank Goldman Sachs International, in his accusation Benny contends the transaction between Goldman and Platinum committed an illegal action of Repo Transaction, and it’s a tort. It is expected that this regulation can provide protection and legal standing related to Repo Transaction in Indonesia.